Features of the Application of Analytical Procedures in the Audit of Property, Plant and Equipment - Abduxomidovich, Aliyev Sherzod (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Methodological aspects of the application of analytical procedures in the audit of property, plant and equipment are studied in the article. As a result of the research, proposals were developed to improve the use of analytical procedures in the audit of property, plant and equipment.